Mama came callin' - Daniels, Ezra Claytan (William Morrow/Harper Alley, 2026)
Kirah was born from an improbable interracial relationship that, in central Florida's infamous Asurupa County, defied all the odds. But her idyllic childhood was shattered by an urban legend come to life. The "Gatorman" was a nightmare on the lips of kids and grown-ups alike all the way back to Jim Crow: a monster with the body of a man, the head of an alligator--and a taste for Black children. That's who crawled into Kirah's window when Kirah was just five years old. According to the police, it was Kirah's own father who put on that gator mask and tried to kill her. Twenty years later, Kirah works hard to build a life unburdened by the traumatic events of her childhood. Just when it seems like she's managed to find her stride, her dad, fresh out of prison, crashes back into her world with a chilling message: "He's coming for you." Finally forced to face the hideous family history she's been avoiding, Kirah sets off to discover where, and who, she truly came from. And the more she learns, the more disturbing the whole picture becomes. Turns out there's a lot more to the Gatorman than Kirah thought, and even worse: he isn't through with her just yet. A clever hybrid of swamp noir, slasher horror, and social satire--and brought to life by Camilla Sucre's vivid illustrations--Mama Came Callin' is a story about family and legacies, both the ones we inherit and the ones we can't escape.